The Influence Of Human Resource Competence And Budget Planning On Budget Absorption At The Regional Secretariat Work Unit Of Kediri City - Lucyana Lucyana; Djunaedi Djunaedi; Budi Rahayu (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of human resource competence and budget planning on budget absorption in the Regional Secretary's Work Unit of Kediri City. The type of research conducted is explanatory, focusing on the cause-and-effect relationships among variables. The analysis results indicate that human resource competence significantly affects budget absorption, with a calculated t value of 9.589, exceeding the t table value of 1.99834. This suggests that improving the quality and management of human resources positively impacts the success of budget absorption. A better understanding of budget management concepts by skilled human resources enhances the effectiveness and efficiency of budget usage. Furthermore, budget planning also has a significant effect, with a calculated t value of 9.003, which is higher than the t table value, indicating the importance of good planning to maximize budget absorption. The alignment between budget planning and implementation, along with effective supervision, is crucial for executing planned programs and activities. This study finds that, overall, 83.9% of the variability in budget absorption can be explained by human resource competence and budget planning, while 16.1% is influenced by other factors such as policies, internal governance, and technology. Recommendations for improvement include enhancing human resource competence through training, improving the planning process, and developing a continuous monitoring and evaluation system. This research provides valuable insights for budget management in local government, particularly in the context of enhancing public service quality in Kediri City.